Morphogenetic processes in the development and evolution of the arteries of the pharyngeal arches: their relations to congenital cardiovascular malformations - Graham, Anthony; Hikspoors, Jill P. J. M.; Lamers, Wouter H.; Anderson, Robert H.; Bamforth, Simon D. (Frontiers in Cell and Developmental Biology, 2023)
The heart and aortic arch arteries in amniotes form a double circulation, taking oxygenated blood from the heart to the body and deoxygenated blood to the lungs. These major vessels are formed in embryonic development from a series of paired and symmetrical arteries that undergo a complex remodelling process to form the asymmetric arch arteries in the adult. These embryonic arteries form in the pharyngeal arches, which are symmetrical bulges on the lateral surface of the head. The pharyngeal arches, and their associated arteries, are found in all classes of vertebrates, but the number varies, typically with the number of arches reducing through evolution. For example, jawed vertebrates have six pairs of pharyngeal arch arteries but amniotes, a clade of tetrapod vertebrates, have five pairs. This had led to the unusual numbering system attributed to each of the pharyngeal arch arteries in amniotes (1, 2, 3, 4 and 6). We, therefore, propose that these instead be given names to reflect the vessel: mandibular (1 st ), hyoid (2 nd ), carotid (3 rd ), aortic (4 th ) and pulmonary (most caudal). Aberrant arch artery formation or remodelling leads to life-threatening congenital cardiovascular malformations, such as interruption of the aortic arch, cervical origin of arteries, and vascular rings. We discuss why an alleged fifth arch artery has erroneously been used to interpret congenital cardiac lesions, which are better explained as abnormal collateral channels, or remodelling of the aortic sac.